Surgical Resection Is Still Better Than Endoscopic Resection for Patients With 2-5 cm Gastric Gastrointestinal Stromal Tumours: A Propensity Score Matching Analysis - Wu, Hao; Li, Han; Xu, Qinfeng; Shang, Liang; Zhang, Ronghua; Li, Chen; Fu, Mengdi; Xu, Wandi; Chen, Jianfeng; Liu, Jin; Li, Leping (Frontiers in Oncology, 2021)
Background. The management of 2-5 cm gastric gastrointestinal stromal tumours (GISTs) is still debated between surgeons and endoscopists. We aimed to investigate short-term and long-term outcomes between surgical resection (SR) and endoscopic resection (ER). Methods. This study included 67 and 215 patients between 2010 and 2020 who underwent ER and SR, respectively. After propensity score matching, the clinical outcomes were compared. Individual patient information that requires special instructions is also summarized. Results. After matching, the operation time (P=0.005) and postoperative hospital stay (P=0.005) were significantly longer in the SR group than in the ER group. However, there were no significant differences in blood loss (P=0.741), resection margin (P=1.000) or time to liquid diet (P=0.055). Statistical differences were also seen in en bloc resection (P<0.001) and adverse events (P=0.027). The recurrence rate did not differ significantly between the two techniques, and the mitotic index and ulceration were identified as independent prognostic factors of progression-free survival. Conclusions. ER might be comparable to SR for the treatment of 2-3 cm gastric GISTs. SR is still considered the standard treatment for 3-5 cm gastric GISTs, while the intraoperative and postoperative information of ER should be recorded in detail and closely evaluated. Surgical resection is recommended if the tumour has a high mitotic index or mucosal ulceration.